2018
DOI: 10.1101/389965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal locomotor learning in mouse cerebellum

Abstract: Stable and efficient locomotion requires precise coordination of whole-body movements. Learned changes in interlimb coordination can be induced by exposure to a split-belt treadmill that imposes different speeds under each side of the body. Here we show that mice adapt to split-belt walking in a way that is remarkably similar to humans, suggesting that this form of locomotor learning is highly conserved across vertebrates. Like human learning, mouse locomotor adaptation is specific to measures of interlimb coo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…2009; Darmohray et al . 2019; Sato & Choi, 2019). There is also evidence that adaptation of asymmetry in step times and step lengths during split‐belt treadmill walking reflect the output of different neural mechanisms: first, step length asymmetry is a combination of both temporal ( when the feet are placed) and spatial ( where the feet are placed) control (Finley et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009; Darmohray et al . 2019; Sato & Choi, 2019). There is also evidence that adaptation of asymmetry in step times and step lengths during split‐belt treadmill walking reflect the output of different neural mechanisms: first, step length asymmetry is a combination of both temporal ( when the feet are placed) and spatial ( where the feet are placed) control (Finley et al .…”
Section: Discussionmentioning
confidence: 99%
“…2012); last, maintenance of the adapted step time asymmetry appears to be prioritized over maintenance of the adapted step length asymmetry (Darmohray et al . 2019; Gonzalez‐Rubio et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that using a split‐belt treadmill training to improve stride length, freezers were unable to adapt the stride time to compensate for differences in leg speed 13 . Split‐belt adaptation (ie, improved stride length) in mice depends on an intact cerebellum 59 . The CLR is involved in the FOG pathophysiology, 24,60 as lesions causing FOG are located within the CLR 24 .…”
Section: Discussionmentioning
confidence: 99%
“…13 Split-belt adaptation (ie, improved stride length) in mice depends on an intact cerebellum. 59 The CLR is involved in the FOG pathophysiology, 24,60 as lesions causing FOG are located within the CLR. 24 These results suggest that freezers are unable to recruit cerebellar networks during successive step to step without reducing the amplitude.…”
Section: Changes In Gait Automaticity Is Associated With Changes In Clrmentioning
confidence: 99%
“…Thus, local networks in the spinal cord and the brainstem are sufficient to generate the basic antagonistic muscle activities that mediate the rhythmic properties of locomotion and breathing, respectively (Tresch et al, 1999; Talpalar et al, 2013; Bellavance et al, 2017; Kurnikova et al, 2017). However, the cerebellum may well play an instrumental role in coordinating front and hind limb movements during more elaborate forms of locomotion adaptation (Hoogland et al, 2015; Machado et al, 2015; Vinueza Veloz et al, 2015; Darmohray et al, 2019) or adjusting the respiratory cycle during more complex tasks such as speech (Deger et al, 1999). Here, we provide evidence that changes in simple spike activity of Purkinje cells in the simplex, crus 1 and crus 2 areas, in which respiratory and whisking processing converges, may contribute to re-adaptation of the respiratory timing signal following sensory perturbation of the facial whiskers.…”
Section: Discussionmentioning
confidence: 99%